PERAN BANK SAMPAH SEMPU DALAM PEMBERDAYAAN EKONOMI MASYARAKAT DESA PASIR GOMBONG KABUPATEN BEKASI - Khoirunnisa, Anis Nurul; Sari, Hesty Puspita (Jurnal Al-fatih Global Mulia, 2021)
The waste bank is one of the programs that exist to deal with waste. Because waste becomes a very serious problem if it is not handled properly. The purpose of this research is to explain the mechanism for managing the Sempu Waste Bank, efforts to empower the customer's economy, and social aspects related to the existence of the Sempu Waste Bank. This type of research uses field research with a qualitative approach. The data sources in this study are managers and customers at the Sempu Waste Bank. Collecting data using observation, interview, and documentation methods. The results of this study can be concluded that the management and role of the Sempu Waste Bank for economic empowerment of the community meets the criteria of being transparent, responsible, profitable, sustainable, extensible, and opening up space for increasing creativity.